COMPREHENSIVE STUDY OF WHOOSH TRAIN DEBT STATUS FROM LEGAL, SOCIAL AND POLITICAL PERSPECTIVES - Hadi Purnomo; Santy; Aklima Thaharuddin; Ihwan Faisal; Rabith Madah Khulaili Harsya (JURNAL ILMIAH EDUNOMIKA, 2026)
The Jakarta-Bandung High-Speed ​​Rail project, known as Whoosh, has transformed from a mere infrastructure ambition to the center of fiscal and national sovereignty debates in Indonesia. This study aims to analyze the debt status of Whoosh through a multidimensional approach encompassing legal, social, and political perspectives until early 2026. Legally, this study highlights the shift in the scheme from a purely Business-to-Business (B2B) to the involvement of the state budget through government guarantees based on Presidential Regulation Number 91 of 2023. From a social perspective, there is a dichotomy between the benefits of public mobility and the tax burden borne by the public due to PT KCIC's operational losses reaching trillions of rupiah. Politically, the sustainability of this project is a test of economic diplomacy between Indonesia and China, especially under the leadership of President Prabowo Subianto who has taken full responsibility for the debt restructuring. The data in this study were collected through a systematic literature review and analysis of recent policy documents. The results of the study indicate that restructuring through the investment agency Danantara is key to maintaining the financial stability of PT KAI as the parent consortium. In conclusion, resolving the Whoosh debt requires stronger regulatory harmonization to mitigate long-term fiscal risks while maintaining public service functions. Keywords: Whoosh, KCIC Debt, Legal Perspective, Infrastructure Politics, Social Impact, Danantara.